Strategies for making artistic research public: a case study of the Uniarts Helsinki Research Pavilion project - Otso Aavanranta; Mika Elo; Leena Rouhiainen (European Journal of Cultural Management and Policy)
This article presents and discusses the Uniarts Helsinki Research Pavilion project, a biennial platform for developing public outreach of artistic research. Launched in 2015, the Research Pavilion has been iterated five times, three editions in the context of the Venice Biennale and two editions in Helsinki, Finland. Drawing on the experience provided by this long-term commitment to foster public outreach of artistic research, the article discusses central management and policy–related negotiations and issues that have become apparent during the Research Pavilion project. In its first part, the article presents the origin and genealogy of the Research Pavilion project, and briefly outlines the operational framing and contexts of its four first editions. The related theoretical underpinnings concerning the development of artistic research are also addressed. In its second part, the text focuses on the latest, fifth iteration of the Research Pavilion, proceeding to critically analyse its policy framework in terms of the cross-pollination as well as the pushes and pulls between academia and independent arts field, the inclusion of an artist-researcher residency programme within the Research Pavilion, and the underlying ethical issues. The article concludes by suggesting that the tensions and negotiations within the Research Pavilion project may reflect the larger context of artistic research, and it discusses possible further steps within a changing macro-political situation.